miR-21 promotes cervical cancer by regulating NTF3 - Yishan Chen; Caiwu Su; Yuke Cai; Lina Ke; Yaxiong Huang (Scientific Reports)
Abstract This study explores the influence of miR-21 and its interaction with the target gene Neurotrophin-3 (NTF3) in cervical cancer (CC). We employed bioinformatics tools, including DIANA, Targetscan, miRDB, and miRDIP, to predict the target genes of miR-21. Immunohistochemistry, RT-qPCR, and Western blotting were performed to quantify the expression levels of miR-21-5p and NTF3 in cervical cancer cells. Additionally, a dual luciferase reporter assay was conducted to examine the specific relationship between miR-21-5P and NTF3. We assessed cell behavior through various tests, including cell viability, scratch wound assays, colony formation, cell invasion experiments, and flow cytometry assays. The dual luciferase reporter assay confirmed that NTF3 is a direct target of miR-21. Overexpression of NTF3 inhibited cell proliferation and migration, while promoting apoptosis, as demonstrated by flow cytometry. Transcriptome sequencing and enrichment analyses (KEGG and GO) revealed NTF3’s involvement in key oncogenic pathways, including PI3K-AKT, MAPK, and calcium signaling. This study underscores the critical role of miR-21 in regulating the proliferation, migration, and apoptosis of cervical cancer cells by targeting NTF3.